Phytoremediation of petroleum hydrocarbon using three mangrove species applied through tidal bioreactor - NURUL HIDAYATI; HAMIM HAMIM; YOHANA C. SULISTYANINGSIH (Biodiversitas Journal of Biological Diversity, 2018)
Hidayati N, Hamim H, Sulistyaningsih YC. 2018. Phytoremediation of petroleum hydrocarbon using three mangrove species applied through tidal bioreactor. Biodiversitas 19: 786-792. Mangrove is important component in coastal ecosystems that often faces environmental pollution including industrial waste, particularly oil waste (petroleum hydrocarbon). This study was aimed to analyze the growth, anatomical, and physiological responses of three mangroves species to petroleum hydrocarbon contaminant applied using tidal bioreactor (ebb flow system) as a model of sea-shore environmental condition. The experiment was carried out using completely randomized design with two factors i.e.: three species of mangrove (Rhizophora sp., Avicennia sp. and Bruguiera sp.) and four levels of petroleum concentration (0%, 10%, 20% and 30%) exposed using tidal bioreactor for 30 days. The parameters observed in this experiment were plant viability, total petroleum hydrocarbon (TPH) of media, plant growth, pH of media and roots malondialdehyde (MDA) content. Leaf anatomy was also analyzed to distinguish accumulation and translocation of oil compounds into leaf tissues. After 30 days of treatments, Rhizophora sp. had the highest viability and was able to reduce the higher level of TPH in the media compared to those of Avicennia sp. and Bruguiera sp. Petroleum hydrocarbon treatment caused the decrease of shoot and root growth of all species, as well as pH of the media, while it significantly increased malondialdehyde of the roots. Anatomical data showed that petroleum hydrocarbon was absorbed and translocated into the guard cell of the stomata. The result shows that Rhizophora sp. was the most tolerant mangrove species to petroleum hydrocarbon compared to Avicennia sp. and Bruguiera sp., indicated by its survival, the decrease of petroleum hydrocarbon in the sediment, and lower MDA content.